High Incidence of Sporadic Creutzfeldt-Jakob Disease in Slovenia in 2015: A Case Series - Tomaž Rus; Bogdan Lorber; Maja Trošt; Srečko Dobrecovič; Nuška Čakš Jager; Mara Popović; Milica G. Kramberger (Dementia and Geriatric Cognitive Disorders Extra, 2018)
Background: Creutzfeldt-Jakob disease (CJD) is a rare fatal neurodegenerative disorder presenting with rapid cognitive decline and additional signs. The clinical characteristics of an increasing number of sporadic CJD (sCJD) patients admitted to the Ljubljana University Medical Centre are presented as well as the incidence of sCJD in Slovenia in 2015 compared to previous years. Methods: We investigated patients presenting with rapidly progressive dementia and at least one additional sign. The diagnosis was made based on clinical diagnostic criteria and an autopsy was performed in all cases. Data on definite sCJD cases in Slovenia since 1999 were obtained and its incidence was calculated. Results: Eight patients with definite sCJD died in 2015 in Slovenia (incidence: 3.89 cases per million). The long-term incidence 1999 was 1.67 per million. Conclusions: The incidence of sCJD was considerably higher in 2015. It reflects fluctuations in sporadic cases of this rare disease. The rising trend might indicate a previous underestimation and better recognition of the disease.